Job Autonomy and Employee Performance: A Study of Central Hospital Agbor, Delta State, Nigeria - Okolie, Ugo Chuks; Egbon, Thomastina Nkechi (Management Research and Behavior Journal, 2023)
The significance of job autonomy on employee performance at central hospital Agbor, Delta State, Nigeria, was investigated in this study. The study used a research survey design to collect data from 150 participants using purposive and basic random sampling methods.  129 copies of the questionnaire were retrieved out of the 150 that were distributed, yielding an 86.0% response rate. Of the 129 respondents in all, 72 were women and 57 were men. The study results demonstrated that job autonomy had an effect on employee performance at central hospital Agbor, Delta State. The study concluded that plethora of evidence supports the positive correlation between worker autonomy and employee performance. When allowing employees to exercise job autonomy, central hospital's management must take certain factors into account. These factors include the employees' skills and abilities, organisational culture, degree of cultural diversity within the organisation, and autonomy limits. Central hospital Agbor should encouraging staff members to get involved in decision-making and empowering them to make decisions within their immediate domain of responsibility after providing them with a general understanding of the policies that govern their operations and utilising job autonomy as a crucial component to improve the effectiveness of staff and the hospital.